Exploring the best tillage option in rice based diversified cropping systems in alluvial soil of eastern India - Kar, Sudeshna; Pramanick, Biswajit; Brahmachari, Koushik; Saha, Goutam; Mahapatra, BS; Saha, Amit; Kumar, Ajay (Soil & tillage research, 2021)
•Reduced tillage (RT) was found to be the most suitable tillage practice•RT increased the system productivity, nutrient recovery and soil microbes•A bit of higher N2O emission was observed in RT than conventional tillage•RT × rice–wheat–greengram system showed higher productivity and total NPK uptake•Better N, K recovery and soil microbes were found in rice–lentil–greengram system Continuous rice–wheat cropping system with intensive conventional tillage operations have been showing natural resource degradation. Hence, the sustainability of this major cropping system in eastern India is under a threat. Adoption of resource conservation such as conservation tillage practice with residue retention on the soil and diversification of the rice–wheat cropping system with the inclusion of pulses, oilseeds may lead towards achieving overall sustainability of the system. Attempts were made to evaluate the different tillage practices viz. zero tillage (ZT), reduced tillage (RT) and conventional tillage (CT) under rice based various cropping systems viz. rice–wheat–greengram, rice–Lathyrus–greengram, rice–lentil–greengram and rice–rapeseed–greengram in terms of system productivity, nutrient uptake by the system, recovery efficiency (RE) of added nutrients, soil microbial population and nitrous oxide (N2O) emission in alluvial soil of eastern India. Results revealed significant increase in system productivity, nutrient uptake and RE of N, P and K in RT. The maximum microbial population was found in ZT. Cereal dominated cropping system (rice–wheat–greengram) showed higher productivity and nutrient uptake, however, the recovery efficiency of nutrient and microbial population was recorded higher in legume dominated cropping systems (rice–lentil–greengram or rice–Lathyrus–greengram). The maximum N2O emission was recorded in ZT, which was almost 3–6% higher than that of RT and CT, respectively. Overall, reduced tillage was found to be the most suitable tillage option under rice based diversified cropping systems.